Somatosensory Evoked Potentials in Children With Bilateral Spastic Cerebral Palsy - Teflioudi, Eleni P.; Zafeiriou, Dimitrios I.; Vargiami, Euthymia; Kontopoulos, Eleutherios; Tsikoulas, Ioannis (Pediatric neurology, 2011)
Alterations were monitored of somatosensory evoked potentials in children with bilateral spastic cerebral palsy and these findings correlated with relevant clinical and laboratory parameters. Fifty-one children with bilateral spastic cerebral palsy (31 boys, 20 girls; age range 24-168 months) participated in the study. Abnormal somatosensory evoked potentials latencies were recorded in 23 of 34 (67.6%) cortical recordings of the median nerve and in 38 of 51 (74.5%) cortical recordings of the tibial nerve. Abnormal tibial nerve somatosensory evoked potentials were strongly correlated with abnormal electroencephalogram ( P = 0.014), while impaired median nerve recordings were correlated with abnormal visual evoked potentials ( P = 0.02) and a history of perinatal or neonatal infection ( P = 0.016). Furthermore, perinatal/neonatal infection adversely effected the recordings in both tibial and medial nerves in quadriplegic patients ( P = 0.023). Sensory impairment is strongly related with abnormal visual evoked potentials, abnormal electroencephalogram, and a history of perinatal or neonatal infection.